Work motivation of employees with different self-presentation strategies - Fofanova, Galina A.; Khikhich, Kristina S. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
Personnel motivation is one of the leading managerial functions in an organization, along with planning, control and coordination. Proper implementation of this function is directly related to the performance indicators of the company as a whole. In this regard, the topic of staff motivation over the past decades continues to be one of the most developed in the framework of organizational psychology and psychology of management. Since working motivation is difficult to express diagnostics, and self-presentation, on the contrary, is an observable phenomenon. Accordingly, a somewhat less controllable component of behavior is the self-presentation strategies used by personnel. A study of how different working motivation of employees with different dominant self-presentation strategies differs will make it possible to develop recommendations for identifying features of work motivation as being more hidden by the observed parameters.